KNOWLEDGE ATTITUDE AND PRACTICE SURVEY ON MANAGEMENT OF NECROTIC IMMATURE PERMANENT TEETH - naram , Abhishek; S, Deepak (International Journal of Psychosocial Rehabilitation, 2020)
Necrotic immature permanent tooth presents a distinctive challenge for the endodontist. Various treatment modalities have been employed to create hard tissue barriers at the apex, Regenerative endodontics is a novel modality which involves physiological replacement of the damaged structures of tooth like dentin, root and cells of the pulp-dentin complex. The aim of this survey was to study the level of awareness, current state of knowledge and opinions towards management of immature necrotic permanent teeth amongst the dental students. An online survey was done with the structured questionnaire based on knowledge, attitude, practice and it was distributed among 100 undergraduate students via electronic media. Data entry was done in the Excel sheet and SPSS software was used to analyze the data. The descriptive statistics were used to determine the responses given by the participants. We received 100 responses from the participants; the majority of the participants are interns (50%). The data from this survey revealed inadequate knowledge of dental students towards management of immature necrotic permanent teeth. Moreover, there is a need to conduct more seminars, CDE and workshop programmes to improve knowledge regarding management of necrotic immature permanent teeth.